Topological stress triggers persistent DNA lesions in ribosomal DNA with ensuing formation of PML-nucleolar compartment - Urbancokova, Alexandra; Hornofova, Terezie; Novak, Josef; Salajkova, Sarka Andrs; Stemberkova Hubackova, Sona; Uvizl, Alena; Buchtova, Tereza; Mistrik, Martin; McStay, Brian; Hodny, Zdenek; Bartek, Jiri; Vasicova, Pavla (eLife, 2024)
PML, a multifunctional protein, is crucial for forming PML-nuclear bodies involved in stress responses. Under specific conditions, PML associates with nucleolar caps formed after RNA polymerase I (RNAPI) inhibition, leading to PML-nucleolar associations (PNAs). This study investigates PNAs-inducing stimuli by exposing cells to various genotoxic stresses. We found that the most potent inducers of PNAs introduced topological stress and inhibited RNAPI. Doxorubicin, the most effective compound, induced double-strand breaks (DSBs) in the rDNA locus. PNAs co-localized with damaged rDNA, segregating it from active nucleoli. Cleaving the rDNA locus with I-PpoI confirmed rDNA damage as a genuine stimulus for PNAs. Inhibition of ATM, ATR kinases, and RAD51 reduced I-PpoI-induced PNAs, highlighting the importance of ATM/ATR-dependent nucleolar cap formation and homologous recombination (HR) in their triggering. I-PpoI-induced PNAs co-localized with rDNA DSBs positive for RPA32-pS33 but deficient in RAD51, indicating resected DNA unable to complete HR repair. Our findings suggest that PNAs form in response to persistent rDNA damage within the nucleolar cap, highlighting the interplay between PML/PNAs and rDNA alterations due to topological stress, RNAPI inhibition, and rDNA DSBs destined for HR. Cells with persistent PNAs undergo senescence, suggesting PNAs help avoid rDNA instability, with implications for tumorigenesis and aging.
Keywords: DNA Damage; PML; cancer biology; Promyelocytic Leukemia Protein; genome maintenance; cellular senescence; poškození DNA; RNA Polymerase I; buněčné jadérko; dvouřetězcové zlomy DNA; human; RNA-polymerasa I; DNA, Ribosomal; aberrant DNA topology; cell biology; Humans; DNA Breaks, Double-Stranded; ribozomální DNA; Cell Nucleolus; protein promyelocytické leukemie; persistent rDNA damage; lidé